AFC with gain adjustment in control system in HDDs for compensation of speaker‐induced vibration. Issue 5 (6th February 2020) - Yabui, Shota; Atsumi, Takenori; Inoue, Tsuyoshi
Abstract : In recent years, hard disk drives (HDDs) have been primarily used in data servers. At the data servers, the head positioning accuracy of control systems is influenced by various external vibrations. The deterioration of the positioning accuracy causes degradation of the digital data transfer rate in the data server. To compensate for the external vibrations in the head positioning systems of HDDs, in this research, the authors developed an adaptive feedforward control (AFC) with a gain learning function. The proposed AFC can update the characteristics of the control system to compensate for the external vibrations in real‐time. This paper reports on the results of experiments in which the proposed AFC is employed to compensate for the speaker‐induced vibration due to buzzing of the data server, implemented to act as notification for any issues occurring in the system. It was noted that the proposed AFC can compensate for the vibrations caused by the buzzing. Moreover, the control parameters updated in real‐time can be used to sense the occurrence of buzzing in the system. © 2020 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.